Direct oral anticoagulants compared to vitamin K antagonists for the treatment of left ventricular thrombi. (3rd October 2022) - Morgan, H; Jones, J; Rathod, K; O'Dowling, R; Pieri, C; Antoniou, S; Mathur, A; Perera, D; Jones, D
Abstract: Background: Left ventricular thrombus (LVT) complicates around one in six cases of acute and chronic left ventricular systolic dysfunction and is associated with an increased risk of stroke, major systemic embolism and death, believed to be ameliorated by anticoagulation. Off-label use of direct oral anticoagulants (DOACs) for LVT has steadily increased, largely based on favourable outcomes in atrial fibrillation and venous thromboembolism, but the safety and efficacy of DOACs versus vitamin K antagonists (VKA) for LVT remains uncertain. Purpose: The main aim of our study was to compare treatment of LVT with VKA to DOAC, focusing on all-cause mortality, stroke, major systemic emboli and major bleeding. Methods: We conducted a retrospective observational longitudinal study of patients presenting to two large quaternary centres between 2011 and 2021 with a diagnosis of LVT. Patients were eligible if they had a documented LVT and received anticoagulation with either VKA or DOAC. Baseline data, thrombus characteristics, treatment type and duration, follow up imaging and clinical events were recorded using electronic health care records. Outcome measures included thrombus resolution, stroke and systemic embolism (SSE), major bleeding and mortality. Results: A total of 955 patients were identified, of whom 901 received treatment with either a VKA (567 pts, 62.9%) or a DOAC (334 pts, 37.1%) and were included in the analysis. Underlying aetiologies included acute myocardial infarction (AMI) (38.3%), chronic ischaemic cardiomyopathy (38.0%) and non-ischaemic cardiomyopathy (23.7%). Rivaroxaban (43.4%) was the most frequently prescribed DOAC followed by apixaban (35.9%), and the remaining on edoxaban (20.7%). AMI related LVT was more commonly treated with DOAC (53.0%) and chronic ischaemic cardiomyopathy with VKA (72.9%). There was a lower baseline LVEF in the VKA cohort (29.5±13.2 vs 33.1±14.2, p<0.0001). Other demographic features were comparable. Median follow up was 2.5 years (IQR: 1–3.5). There were no differences in follow up duration between the two treatments (p=0.17). Greater rates of thrombus resolution were seen in the DOAC group compared to VKA (1 year: 78.4% vs 51.4%, p<0.0001), with higher rates of persistent thrombus over the follow-up period seen in the VKA group (25.1% vs 12.9%, p<0.0001). Rates of stroke and systemic embolization were similar between the groups (VKA 9.3% vs 9.6% DOAC, p=0.93). Higher rates of bleeding (BARC >3, 8.1% VKA, 3.6% DOAC, p=0.031) (Figure 1A) and mortality (VKA 18.5%, DOAC 10.2%, p=0.001) (Figure 1B) were seen in the VKA group over the follow-up period. Conclusions: In a large multi-centre registry of LVT of mixed aetiology, anticoagulation with DOAC was associated with earlier and greater rates of thrombus resolution and consequential reduced adverse events (major bleeding and mortality) during follow up. A funding application to support a multi-centre randomised control trial is underway. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): This work was supported by the British Heart Foundation (Fellowship FS/CRTF/21/24190 to HM) and the National Institute for Health Research (Biomedical Research Centre Award to Guy's and St Thomas' NHS FT and King's College London).